MODELLING OF IRAQI GYPSEOUS SOIL BEHAVIOUR UNDER STRESS-FLOW-DISSOLUTION CONDITIONS (Journal of Engineering, 2008)
Gypseous soils are distributed in many regions in Iraq. Therefore, it is necessary to study the geotechnical properties of such soils due to the possible large damage that may incur structures founded and constructed in or on them. The soil used in this study is from Al-Najef City, Iraq. It is poorly graded sand. It also has a gypsum content of about 28-32٪. The mineralogical and chemical properties of the soil are established at first. However, this study is concerned with the dissolution of gypsum and its effect on the soil. The importance of the progress of dissolution is verified through the study of the characteristics of the soil skeleton and the pore fluid. Three differential equations are used to study this effect, namely, continuity, equilibrium and dispersion. They are solved by using the finite element method. In addition, this work uses the hyperbolic stress-strain idealization as a constitutive relationship. Tri-axial (CD) tests are conducted to find the hyperbolic parameters. An experimental setup is modified to find the longitudinal and lateral coefficients of dispersion. One- and twodimensional problems are solved to study the effect of dissolution. Results reveal high effectsof dissolution of gypsum on the settlement, pore water pressure, elastic modulus and Poisson's ratio values. Settlement increases while other parameters (E, B and υ) decrease with increasing dissolution. Furthermore, there is a vast behavioral difference between one and two dimensional problems.